H-mode achieved by pellet injection in experimental advanced superconducting tokamak. (11th April 2017) - Yao, X.J.; Hu, J.S.; Chen, Y.; Sun, Z.; Liu, H.Q.; Lian, H.; Wang, S.X.; Jie, Y.X.; Shi, N.; Xu, G.S.; Yang, Q.Q.; Shi, T.H.; et al.
Abstract: High-confinement (H-mode) plasma was achieved by injecting frozen deuterium pellets in the experimental advanced superconducting tokamak (EAST). Interesting phenomena of the simple and two-stage low–high confinement (L–H) transitions are observed in EAST with radio frequency heating after pellet injection. The results of the L–H transitions induced by pellets are discussed in detail with different theories. It is found that pellet injection in EAST can reduce the power threshold of the H-mode. Furthermore, the pellet-induced edge density gradient is an important parameter affecting the L–H transition. This investigation would be useful for the analysis of the feasibility of H-mode access by pellet injection in future devices, such as ITER.